Revisiting the effectiveness of economic sanctions in the context of Russia's invasion of Ukraine - Tsouloufas, George; Rochat, Matthew (Canadian foreign policy journal, 2023)
This paper addresses the relevant and ongoing debate surrounding the effectiveness of economic sanctions. In light of recent sanctions imposed by Canada, the United States, Europe, and other Western states in response to Russia's invasion of Ukraine, the topic has garnered renewed attention. To assess the effectiveness of these sanctions thus far, it is important to revisit key contributions in the existing literature. We begin by defining economic sanctions and describing their most common forms. Next, we explore the question of whether sanctions are effective, by examining different conceptions of the term "effectiveness." Then, we address the skeptics to understand why many scholars have argued that sanctions tend to be ineffective or have adverse consequences. Finally, we examine the key question of the effectiveness of economic sanctions thus far in the context of Russia's invasion of Ukraine, utilizing a five-dimensional framework devised by Lindsay (1986. Trade sanctions as policy instruments: A Re-examination. International Studies Quarterly, 30(2), 153-173). We find evidence that the sanction regime on Russia has been mostly effective thus far in dimensions of deterrence, international symbolism, and domestic symbolism, partially effective in terms of compliance, and mostly ineffective in terms of subversion. We conclude by arguing that future research should take a broader, more interdisciplinary approach when assessing sanction effectiveness.